In Situ Mechanistic Elucidation of Superior Si‐C‐Graphite Li‐Ion Battery Anode Formation with Thermal Safety Aspects. Issue 2 (22nd November 2019) - Parekh, Mihit H.; Sediako, Anton D.; Naseri, Ali; Thomson, Murray J.; Pol, Vilas G.
Abstract: A composite anode material synthesized using silicon nanoparticles, micrometer sized graphite particles, and starch‐derived amorphous carbon (GCSi) offers scalability and enhanced electrochemical performance when compared to existing graphite anodes. Mechanistic elucidation of the formation steps of tailored GCSi composite are achieved with environmental transmission electron microscopy (ETEM) and thermal safety aspects of the composite anode are studied for the first time using specially designed multimode calorimetry for coin cell studies. Electrochemical analysis of the composite anode demonstrates a high initial discharge capacity (1126 mAh g −1 ) and yields a high coulombic efficiency of 83% in the first charge cycle. Applying a current density of 500 mA g −1, the anode composite retains 448 mAh g −1 specific capacity after 100 cycles. Cycling stability is a result of improved interfacial binding made possible by the interconnected architecture of wheat derived amorphous carbon, enhancing the electrochemical kinetics and decreasing the inherent issues associated with volume expansion and pulverization of pristine Si electrodes. Comparing the energy released during thermal runaway, per specific capacity for the full‐cell, the GCSi composite releases less heat than the conventional graphitic anode, suggesting a synergistic effect of each ingredient of the GCSi composite, providing a safer and higher performing anode. Abstract : A novel composite anode containing 25 wt% Si‐nanoparticles interfaced to graphite with starch derived carbon delivers an initial capacity of 638 mAh g −1 at a current density of 500 mA g −1 . The thermal studies of the composite anode yields lower exothermic heat compared to commercially used graphite, demonstrating progress toward safer anodes.